Use of double-phase-sensitive detection to measure DPOAE signals - Michalski, Wojciech; Dziewiszek, Wojciech; Bochnia, Marek (Archives of Acoustics, 2007)
This paper presents a new method of measuring distortion product otoacoustic emissions(DPOAE) induced by a two-tone acoustic wave. The method is based on double-phasesensitivedetection whereby it is possible to precisely measure DPOAE signals whose acousticpressure level is even below −15 dB. Exemplary experimental results for guinea pigs aregiven.